ANALISIS LITERASI SISWA KELAS IV SDN GAYAMSARI 02 KOTA SEMARANG MELALUI MEDIA KOMIK BERORIENTASI PROFIL PELAJAR PANCASILA - Aulia Sifa Lia; Ari Widyaningrum; Sunan Baedowi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The background that prompted this research was that there were still a number of students in grade IV who were still difficult to move to read so that it would affect students' literacy skills (students' low interest in reading). This was proven when students were asked by the class teacher about what they had read, but these students did not understand the contents of the reading. The purpose of this study was to analyze the literacy of fourth grade students at SDN Gayamsari 02 Semarang through comic media oriented to Pancasila student profiles. This type of research was descriptive-qualitative research using interview, observation, questionnaire and documentation methods. The subjects in this study were fourth grade students at SDN Gayamsari 02 Semarang, totaling 31 students and were processed by source and technique triangulation. The results of this study indicate that the reading literacy of fourth grade students through comic media is 70.06% good which includes literal reading skills, critical reading and creative reading. Comic media oriented to Pancasila student profiles chosen by the teacher as literacy media in class IV SDN Gayamsari 02 Semarang City can provide a positive response, namely increasing literacy skills, student activity and students' interest in reading because the text is short so it is easy to understand, contains colorful pictures, character recognition in comics and dialogue stories that make students participate imaginatively in their minds and students are directed their awareness to apply the values of the Pancasila student profile, especially on the value of being independent, critical and creative thinking. It can be concluded that comic media orientated on Pancasila student profiles can increase students' reading interest and reading literacy skills in Class IV SDN Gayamsari 02 Semarang City. Keywords: student literacy, comic media, Pancasila student profiles